Rancang Bangun Data Logger Kecepatan Angin Untuk 4 Level Ketinggian Berbasis Arduino - Awang Bagaskoro; Antonius Rajagukguk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Wind energy is one of the renewable energy sources that can be used as a power plant to meet the needs of electrical energy in an area. The potential for wind energy in an area can be determined based on the wind speed. Each area has a wind speed that varies, depending on the shape of the wind trajectory and the obstacles in the area. Therefore, information about wind speed is needed to see the potential for wind energy in an area. This study tries to design a tool that can record wind speed (data logger) with 4 variations in altitude based on the Arduino microcontroller, where the measurement results from the tool will be stored on the SD Card. Measurement of wind speed with altitude variations aims to see at what altitude level wind energy can be utilized. This research was conducted in the Riau University area starting on March 30 - April 5, 2021. The average percentage error of Final Project anemometer readings is 3% compared to standard anemometer readings. The results of measurements in the Riau University area found that the highest average wind speed was 1.80 m/s. While the maximum wind speed during the study was 6.51 m/s. The highest wind potential occurs on Friday with a power of 11.02 W and wind energy of 140.25 Wattday.Keyword : Energy, Wind Speed, Anemometer, Data logger